Impact of Consumer and FinTech Characteristics on FinTech Resistance: A Study from User Perspective - Aiman Sultan; Ammara Mubashar; Um-e-Rubbab (NUML International Journal of Business & Management)
The study's objectives are to identify the characteristics of customers and FinTech apps that resist using FinTech services in the era of technology. Consumer characteristics studied in this study were consumer-perceived digital self-efficacy and consumer-perceived digital knowledge. FinTech characteristics were perceived digital security concerns and perceived digital complexity.  Moreover, the research aimed to determine if consumers' techno-stress moderates the relationship between consumer characteristics and their resistance to FinTech. The model was supported by innovation resistance theory. Convenience sampling was used to gather data from 384 bank account holders from Rawalpindi and Islamabad. Adapted questionnaires with five-point Likert scales for each variable were used. Results indicated that all consumer characteristics have a negative and significant relationship with FinTech resistance. However, among FinTech characteristics, only perceived digital complexity positively influenced FinTech resistance, and the impact of perceived digital complexity was not found on FinTech resistance. The moderating role of techno-stress among all consumer characteristics and FinTech resistance was supported. The Moderating role of techno-stress was supported between FinTech characteristics i.e. perceived digital security and FinTech resistance but not supported between perceived digital concern and FinTech resistance. The findings suggest that educational initiatives, such as workshops, seminars, and online resources, can empower users with knowledge about FinTech solutions, thereby reducing perceived risk and resistance. Regular app reviews will help the organization adapt to evolving challenges and best practices in FinTech adoption.